IS IT POSSIBLE TO USE BEVACIZUMAB BIOSIMILAR IN ALL INDICATIONS REGISTERED FOR ORIGINAL DRUG? - S. V. Orlov; N. L. Shimanovskii; S. N. Fogt (Исследования и практика в медицине)
The possibility of extrapolation of indications for biosimilars is one of the issues widely discussed in modern literature. Currently, the European Medicines Agency (EMA) and the Food and Drug Administration (FDA) have identified specific conditions under which for biosimilars extrapolation of indications is possible. In2015, athe first bioanalogue bevacizumab, (produced by JSC "BIOCAD"), has been registered. The article provides summary of the pivotal clinical study of Bevacizumab bioanalogue conducted in patients with non-small cell lung cancer. The article includes detailed scientific justification for the extrapolation of data on the efficacy, safety and immunogenicity obtained in the pivotal study to other indications, registered for the original bevacizumab drug.